A Revealed Preference Analysis of Asset Pricing Under Recursive Utility - Epstein, L. G.; Melino, A. (Review of Economic Studies, 1995)
This paper considers a representative agent model of asset prices based on a recursive utility specification. A constant elasticity of intertemporal substitution is assumed but the risk-preference component of utility is restricted only by qualitative, non-parametric regularity conditions. A principal contribution is to determine the exhaustive implications of this semiparametric recursive utility model for the one-step ahead joint probability distribution for consumption growth and asset returns. It is also shown, in contrast to the claims of previous studies, that the generalization from expected utility to recursive utility contributes substantially to the resolution of the equity premium puzzle.